Development and validation of a rapid liquid chromatography/tandem mass spectrometry method to quantitate gabapentin and buprenorphine in human serum. (30th May 2021) - Phillips, Sarah J.; Oliveto, Alison; Mancino, Michael J.; Hendrickson, Howard P.
Abstract : Rationale: Gabapentin has shown initial promise as an opioid‐sparing medication in pain patients as well as a treatment for opioid withdrawal and liquid chriomatography/tandem mass spectrometry (LC/MS/MS) is often used for clinical monitoring. Despite reports of validated tandem mass spectrometric methods for the determination of gabapentin and buprenorphine, mechanisms for the collision‐induced fragmentation have not been adequetely described. Methods: A rapid analytical method has been developed to determine gabapentinoid, gabapentin, and the partial opioid agonist, buprenorphine, in 20 μL of human serum using LC/MS/MS with a chromatographic run time of 2 min. A simplified sample cleanup procedure using methanol precipitation of serum proteins/lipids followed by evaporation and reconstitution in mobile phase was demonstrated. Gabapentin and buprenorphine were detected following positive ion electrospray ionization using multiple‐reaction monitoring. The internal standard approach was used for quantitation with labeled gabapentin‐D10 and buprenorphine‐D4 serving as internal standards. Using organic reaction principals and stable isotope labels, collision‐induced fragmentation mechanisms for both gabapentin and buprenorphine are proposed. The method was validated according to the FDA Guidance for Industry – Bioanalytical Method Validation. Results: Accuracy was demonstrated by error values ≤15% for buprenorphine and ≤6% for gabapentin. The inter‐day precision was ≤4.88% and 15.59% for gabapentin and buprenorphine and the intra‐day precision was ≤5.20% and 11.65% for gabapentin and buprenorphine. The lower limit of quantitation corresponded to 10 ng/mL for gabapentin and 1 ng/mL for buprenorphine in serum. Recoveries were 104 ± 2.55% and 85 ± 2.03% for gabapentin and buprenorphine, respectively. Conclusions: Concentrations of gabapentin and buprenorphine were determined for five authentic human serum samples to further validate the utility of the method and applicable to therapeutic drug monitoring beyond its use as a drug screening assay. Furthermore, new mechanisms for the collision‐induced dissociation of gabapentin and buprenorphine have been proposed.